Assessing University Students' Critical Online Reasoning Ability: A Conceptual and Assessment Framework With Preliminary Evidence - Molerov, Dimitri; Zlatkin-Troitschanskaia, Olga; Nagel, Marie-Theres; Brückner, Sebastian; Schmidt, Susanne; Shavelson, Richard J. (Frontiers in Education, 2020)
Critical evaluation skills when using online information are considered important in many research and education frameworks; critical thinking and information literacy are cited as key 21st century skills for students. Higher education may play a special role in promoting students’ skills in critically evaluating (online) sources. Today, higher education students are more likely to use the Internet instead of offline sources such as textbooks when studying for exams. However, far from being a value-neutral, curated learning environment, the Internet poses various challenges, including a large amount of incomplete, contradictory, erroneous, and biased information. With low barriers to online publication, the responsibility to access, select, process, and use suitable relevant and trustworthy information rests with the (self-directed) learner. Despite the central importance of critically evaluating online information, its assessment in higher education is still an emerging field. In this paper, we present a new developed theoretical-conceptual framework for Critical Online Reasoning (COR), situated in relation to prior approaches ('information problem-solving', 'multiple-source comprehension', 'web credibility', 'informal argumentation', 'critical thinking'), along with a evidence-centered assessment framework and its preliminary validation. In 2016, the Stanford History Education Group developed and validated the assessment of Civic Online Reasoning for the United States. At the college level, this assessment holistically measures students' web searches and evaluation of online information using open Internet searches and real websites. Our initial adaptation and validation indicated a need to further develop the construct and assessment framework for measuring higher education students in Germany across disciplines over their course of studies. Based on our literature review and prior analyses, we classified COR performance into three uniquely combined facets: (i) online information acquisition, (ii) critical information evaluation, and (iii) reasoning based on evidence, argumentation, and synthesis. We modeled COR ability from a behavior, content, process, and development perspective, specifying scoring rubrics in an evidence-centered design. Preliminary validation results from expert interviews and content analysis indicated that the assessment covers typical online media and challenges for higher education students in Germany and contains cues to tap modelled COR abilities. We close with a discussion of ongoing research and potentials for future development.